(untitled) (International Journal of Scientific Trends, 2026)
This article examines the assessment of regulatory impact as a tool for preventing corruption in the preparation of regulatory legal acts in the Republic of Uzbekistan. It is substantiated that corruption is caused not only by the illegal behavior of officials, but also by defects in regulatory regulation, including the uncertainty of legal formulations, excessive discretionary powers and non-transparency of administrative procedures. based on the concept of assessing the corruption impact of regulation, and the importance of the participation of civil society institutions in this process is emphasized. It is concluded that it is necessary to include mechanisms for preventing corruption risks in the RIA procedures.